Covalently Attached Hollow Capsules Resistant to Etching of Polar Solution - Guo, S.L.; Guo, N.; Zheng, J.; Wang, Y.; Yan, X.F.; Wang, Z.Y. (Asian Journal of Chemistry, 2012)
Hollow capsules with nano-scaled walls were prepared by electrostatic layer-by-layer deposition of diazo-resin in alternation with nafion onto microparticles templates, followed by dissolution of the cores with acid solution or organic solvent. The stepwise growth of multilayers was followed by UV/VIS spectra. The formation of hollow capsules was verified by confocal laser scanning microscopy and atomic force microscopy. After application of UV irradiation, the linkage of hollow capsules was converted form an ionic bond to a covalent bond and the conversion was verified by FTIR and UV/VIS spectra. As a result, the stability of hollow capsules to polar solution increased dramatically.